2020
DOI: 10.1186/s12870-019-2229-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced concomitant increases in photosynthesis, respiration, and C, N and S assimilation revealed by transcriptomic analyses in Ulva compressa (Chlorophyta)

Abstract: Background: The marine alga Ulva compressa is the dominant species in copper-polluted coastal areas in northern Chile. It has been shown that the alga tolerates micromolar concentrations of copper and accumulates copper at the intracellular level. Transcriptomic analyses were performed using total RNA of the alga cultivated with 10 μ M copper for 0, 1, 3 and 5 days using RNA-seq in order to identify processes involved in copper tolerance. Results: The levels of transcripts encoding proteins belonging to Light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In addition, NADPH produced by G6PDH may be consumed to increase C, N and S assimilation, which are processes requiring NADPH, in the cytoplasm (Kopriva et al, 1999;Kopriva et al, 2002). In this sense, it has been shown that C, N and S assimilation is increased in the alga exposed to copper excess since the level of transcripts and the activities of key enzymes involved in these processes are also increased (Laporte et al, 2020). The enhanced C, N and S assimilation may be required to the synthesis of new proteins and membranes that are damaged by copper-induced oxidative stress.…”
Section: Copper-induced Increase In Hk L-gldh Gs and G6pdh Activitimentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, NADPH produced by G6PDH may be consumed to increase C, N and S assimilation, which are processes requiring NADPH, in the cytoplasm (Kopriva et al, 1999;Kopriva et al, 2002). In this sense, it has been shown that C, N and S assimilation is increased in the alga exposed to copper excess since the level of transcripts and the activities of key enzymes involved in these processes are also increased (Laporte et al, 2020). The enhanced C, N and S assimilation may be required to the synthesis of new proteins and membranes that are damaged by copper-induced oxidative stress.…”
Section: Copper-induced Increase In Hk L-gldh Gs and G6pdh Activitimentioning
confidence: 99%
“…In addition, the constant level of NADPH that did not change with inhibitors of CaMKs, CDPKs and MAPKs indicates that the constant NADPH level is due to photosynthesis. In this sense, it was shown that net photosynthesis is increased in the alga exposed to copper excess for 0 to 5 days (Laporte et al, 2020) and the increase in NADPH level is due to activation of ferredoxin-NADPH reductase (FNR) in chloroplasts. It has been shown FNR is not regulated by phophorylation but instead by acetylation of a lysine residue located near the active site in A. thaliana (Lethimäki et al, 2014).…”
Section: Copper-induced Increase In Hk L-gldh Gs and G6pdh Activitimentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic analyses were performed with alga cultivated with 10 M of copper for short times such as 0, 3, 6, 12 and 24 h and longer times such as 0, 1, 3 and 5 d in order to find new UcMTs and probably a PCS [ 52 , 53 ]. Transcriptomic analyses performed for long times allowed the identification of two potential new UcMTs, but not a PCS.…”
Section: Additional Mechanisms Of Copper Tolerance In the Marine Mmentioning
confidence: 99%